2011
DOI: 10.1177/1363460711420463
|View full text |Cite
|
Sign up to set email alerts
|

‘Deep down where the music plays’: How parents account for childhood gender variance

Abstract: Parents of gender variant children routinely negotiate their child's gender with social institutions, from schools to churches to neighborhood associations. These interactions require that parent develop narratives about why their particular child violates gender norms. In this paper, I argue that over the last century, there has been a proliferation within biomedicine, psychiatry and popular culture of the ways in which we can “know” gender; and as a result, ever more emotional work is required to account for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
73
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(76 citation statements)
references
References 61 publications
3
73
0
Order By: Relevance
“…Sexual minority parents also exist in a society that renders queer parenting in general subject to especially intense scrutiny (Lev, ). Perhaps not surprising, then, was the finding that others blamed some of our queer participants for their children being trans*, similar to previously reported accounts (Hill & Menvielle, ; Lev, ; Meadow, ; Rahilly, ; Sansfaçon et al, ). In addition to causing distress for parents, blame reactions reify cisnormativity by suggesting that trans* identities are wrong, shameful, and unnatural.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Sexual minority parents also exist in a society that renders queer parenting in general subject to especially intense scrutiny (Lev, ). Perhaps not surprising, then, was the finding that others blamed some of our queer participants for their children being trans*, similar to previously reported accounts (Hill & Menvielle, ; Lev, ; Meadow, ; Rahilly, ; Sansfaçon et al, ). In addition to causing distress for parents, blame reactions reify cisnormativity by suggesting that trans* identities are wrong, shameful, and unnatural.…”
Section: Discussionsupporting
confidence: 89%
“…As such, we wanted to know how these participants both challenged and were influenced by internalized heteronormativity and, more specifically, cisnormativity in their everyday lives. Our findings echo those found in case studies of lesbian mothers with trans* children (Lev, ; Saeger, ) and larger studies of primarily heterosexual parents with trans* children (Hill & Menvielle, ; Meadow, ; Rahilly, ; Sansfaçon et al, ). The findings also build on these previous studies by offering new insights.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…As discussed earlier, however, medicalisation does not have a unidirectional impact and has the potential to operate as an empowering as well as a constraining force in everyday life. Many scholars have shown that the medical model restricts trans people in legal, social and medical settings while simultaneously providing avenues to gender‐affirming care (Burke , Butler , Koenig , Meadow , , Romeo , Spade , ). The double‐edged effects of trans diagnosis arise most noticeably in the form of gatekeeping, or the use of the medical model and associated diagnostic standards as a normative accountability structure (Johnson , ) that empowers trans people who fit its criteria and constrains those who do not.…”
Section: Medicalisation Of Trans Experiencementioning
confidence: 99%
“…These are the kids who may go on to transition to a new gender role. In Meadow's (2011) study of parents of gender non-conforming children, a mother asks her daughter Willow (who was once her son): ''How do you know you're a girl?'' to which Willow answered: ''I know, because I feel it deep down where the music plays'' (p. 740).…”
Section: Jordan Raine and Willow: The Faces Of Gender Independent Kidsmentioning
confidence: 99%